Blockade of CTLA-4 promotes the development of effector CD8(+) T lymphocytes and the therapeutic effect of vaccination with an attenuated protozoan expressing NY-ESO-1. - Dos Santos, L; Galvão-Filho, B; de Faria, P; Junqueira, C; Dutra, MS; Teixeira, S; Rodrigues, M; Ritter, G; Bannard, O; Fearon, D; Antonelli, L; Gazzinelli, RT (Springer Berlin Heidelberg, 2015)
The development of cancer immunotherapy has long been a challenge. Here, we report that prophylactic vaccination with a highly attenuated Trypanosoma cruzi strain expressing NY-ESO-1 (CL-14-NY-ESO-1) induces both effector memory and effector CD8(+) T lymphocytes that efficiently prevent tumor development. However, the therapeutic effect of such a vaccine is limited. We also demonstrate that blockade of Cytotoxic T Lymphocyte Antigen 4 (CTLA-4) during vaccination enhances the frequency of NY-ESO-1-specific effector CD8(+) T cells producing IFN-γ and promotes lymphocyte migration to the tumor infiltrate. As a result, therapy with CL-14-NY-ESO-1 together with anti-CTLA-4 is highly effective in controlling the development of an established melanoma.